Targeting the NLRP3/Caspase-1 pyroptotic pathway exacerbates insulin resistance upon exposure to nanoplastics with different surface chemistries - Xinxin Yao; Yu Cao; Sue Lin; Shihua Chen; Feiqin Xie; Wenhui Xu; Yize Wu; Qiufang Wu; Renyi Peng; Xiaohua Gong (Journal of Hazardous Materials, 2026)

Pioneering sustainable governance reporting: A novel governance-life cycle assessment framework - Seok Peng Ngan; Sue Lin Ngan; DongHui Zhao; Puan Yatim; Mohd Helmi Ali; Hon Loong Lam (Sustainable Production and Consumption, 2026)

Real-time satellite monitoring of the 2024–2025 dyke intrusion sequence at Fentale-Dofen volcanoes, Ethiopia - Lin Way; Juliet Biggs; Weiyu Zheng; Milan Lazecky; Edna W. Dualeh; Tim Wright; Raphaël Grandin; Arthur Hauck; Sue Loughlin; Julia Crummy; Elias Lewi (Bulletin of Volcanology, 2025)

Demystifying priority of deploying sustainable petrochemical waste management: Multi-Stakeholder insights from a developing country - Mei Kuen Wang; Juin Yau Lim; ZiYu Lin; Sue Lin Ngan; Yi Jing Chan; Hon Loong Lam (Journal of Cleaner Production, 2025)

PLATZ transcription factors and their emerging roles in plant responses to environmental stresses - Hongxia Zhang; Lu Liu; Zhenzhen Li; Shuo Wang; Li Huang; Sue Lin (Plant Science, 2025)

Correction to: Anti-cancer strategies targeting the autotaxin-lysophosphatidic acid receptor axis: is there a path forward? - Gábor Tigyi; Mélanie A. Dacheux; Kuan-Hung Lin; Junming Yue; Derek Norman; Zoltán Benyó; Sue Chin Lee (Cancer and Metastasis Reviews, 2024)

The roles of non-coding RNAs in male reproductive development and abiotic stress responses during this unique process in flowering plants - Dexi Shi; Huiting Huang; Yuting Zhang; Zhihao Qian; Jiao Du; Li Huang; Xiufeng Yan; Sue Lin (Plant Science, 2024)

Satellite observations reveal a decreasing albedo trend of global cities over the past 35 years - Shengbiao Wu; Xingwen Lin; Zunjian Bian; Mathew Lipson; Raffaele Lafortezza; Qiang Liu; Sue Grimmond; Erik Velasco; Andreas Christen; Valéry Masson; Ben Crawford; Helen Claire Ward; et al. (Remote Sensing of Environment, 2024)

Treatment of Lateral Canthal Lines With RelabotulinumtoxinA, an Investigational Liquid Botulinum Toxin: Clinical Efficacy and Safety Results From the READY-2 Phase 3 Trial - Glynis Ablon; David Bank; Theda Kontis; Sherrif F Ibrahim; Melanie Palm; Sue Ellen Cox; Jason K Rivers; Lisa Grunebaum; Mitchel P Goldman; Shannon Humphrey; Xiaoming Lin; Schafiq Nabhani; et al. (Toxicon, 2024)

MYB transcription factors and their roles in the male reproductive development of flowering plants - Yijie Wang; Huiyan Zhou; Yuanrong He; Xiuping Shen; Sue Lin; Li Huang (Plant Science, 2023)

Current status and perspectives of algae-based bioplastics: A reviewed potential for sustainability - Wai Yan Cheah; Ah Choy Er; Kadaruddin Aiyub; Nazlina Haiza Mohd Yasin; Sue Lin Ngan; Kit Wayne Chew; Kuan Shiong Khoo; Tau Chuan Ling; Joon Ching Juan; Zengling Ma; Pau Loke Show (Algal Research, 2023)

Upcycling textile waste using pyrolysis process - Hee Sue Lee; Sungyup Jung; Kun-Yi Andrew Lin; Eilhann E. Kwon; Jechan Lee (Science of The Total Environment, 2023)

Nitric Oxide Alleviates Submergence-Induced Maize Seedling Root Tip Cell Death - Yaoqi Li; Qiong Nan; Yinai Liu; Sue Lin; Hao Ji; Da Sun; Libo Jin; Renyi Peng (Journal of Plant Growth Regulation, 2023)

Anti-cancer strategies targeting the autotaxin-lysophosphatidic acid receptor axis: is there a path forward? - Gábor Tigyi; Mélanie A. Dacheux; Kuan-Hung Lin; Junming Yue; Derek Norman; Zoltán Benyó; Sue Chin Lee (Cancer and Metastasis Reviews, 2021)

Correction to: Reprogramming of gene expression in Escherichia coli cultured on pyruvate versus glucose - Anna Chao Kaberdina; Olatz Ruiz-Larrabeiti; Sue Lin-Chao; Vladimir R. Kaberdin (Molecular Genetics and Genomics, 2019)

Reprogramming of gene expression in Escherichia coli cultured on pyruvate versus glucose - Anna Chao Kaberdina; Olatz Ruiz-Larrabeiti; Sue Lin-Chao; Vladimir R. Kaberdin (Molecular Genetics and Genomics, 2019)

Wake Characteristics of Tall Buildings in a Realistic Urban Canopy - Denise Hertwig; Hannah L. Gough; Sue Grimmond; Janet F. Barlow; Christoph W. Kent; William E. Lin; Alan G. Robins; Paul Hayden (Boundary-Layer Meteorology, 2019)

The putative pectin methylesterase gene, BcMF23a, is required for microspore development and pollen tube growth in Brassica campestris - Xiaoyan Yue; Sue Lin; Youjian Yu; Li Huang; Jiashu Cao (Plant Cell Reports, 2018)

Design of alternate solvent for recovery of residual palm oil: simultaneous optimization of process performance with environmental, health and safety aspects - Sarah Sue Lin Chang; Yuan Lin Kong; Wei Xuen Lim; Jecksin Ooi; Denny K. S. Ng; Nishanth G. Chemmangattuvalappil (Clean Technologies and Environmental Policy, 2018)

Correction to: Age at menarche and age at natural menopause in East Asian women: a genome-wide association study - Jiajun Shi; Ben Zhang; Ji-Yeob Choi; Yu-Tang Gao; Huaixing Li; Wei Lu; Jirong Long; Daehee Kang; Yong-Bing Xiang; Wanqing Wen; Sue K. Park; Xingwang Ye; et al. (GeroScience, 2018)

Overview of the key risks in the pioneering stage of the Malaysian biomass industry - Puan Yatim; Ngan Sue Lin; Hon Loong Lam; Er Ah Choy (Clean Technologies and Environmental Policy, 2017)

Characterization of BcMF23a and BcMF23b, two putative pectin methylesterase genes related to pollen development in Brassica campestris ssp. chinensis - Sue Lin; Li Huang; Xiaolin Yu; Xingpeng Xiong; Xiaoyan Yue; Tingting Liu; Ying Liang; Meiling Lv; Jiashu Cao (Molecular Biology Reports, 2017)

Developing Single Nucleotide Polymorphism (SNP) Markers for the Identification of Coffee Germplasm - Lin Zhou; Fernando E. Vega; Huawei Tan; Aixa E. Ramírez Lluch; Lyndel W. Meinhardt; Wanping Fang; Sue Mischke; Brian Irish; Dapeng Zhang (Tropical Plant Biology, 2016)

Double homeobox gene, Duxbl, promotes myoblast proliferation and abolishes myoblast differentiation by blocking MyoD transactivation - Shey-Lin Wu; Guo-Zili Li; Chin-Yi Chou; Ming-Shiun Tsai; Yi-Pei Chen; Chung-Jung Li; Gan-Guang Liou; Wen-Wei Chang; Shen-Liang Chen; Sue-Hong Wang (Cell and Tissue Research, 2014)

Strengthening of paleo‐typhoon and autumn rainfall in Taiwan corresponding to the Southern Oscillation at late Holocene - Huei‐Fen Chen; Shie‐Ying Wen; Shen‐Rong Song; Tien‐Nan Yang; Teh‐Quei Lee; Sue‐Fen Lin; Shih‐Chieh Hsu; Kuo‐Yen Wei; Ping‐Yu Chang; Pai‐Sen Yu (Journal of Quaternary Science, 2012)
The purpose of this study is to improve prehistoric knowledge of paleo‐typhoon and winter monsoon activity in the western North Pacific after 8 cal. ka BP. We examine two sediment cores derived from lakes located to the south and north of the Ilan Plain in northeastern Taiwan. Seasonal and typhoon rainfall data over the past several decades are collected for this study region. We also use mineral indicators, K/Rb ratios and grain size to estimate sediment sources, intensity of chemical weathering and rainfall intensity. The results show that the chemical weathering index (K/Rb ratio) of Meihua Lake indicates the continuing effects of autumn rainfall, while coarse grain sizes of Dahu Lake sediments suggest increased intensity in typhoon rainfall. Grain size results reveal that increasing El Niño–Southern Oscillation intensity in the tropical Pacific has intensified the activity of super typhoons in the western North Pacific. Finally, we find that frequent activity of super paleo‐typhoons occurred in Taiwan during the La Niña‐like state, and the strengthening winter monsoon activity and higher sea surface temperature enhanced plentiful autumn rainfall in El Niño‐like state. After comparing our results with the paleo‐typhoon data in Japan and south China, we suggest that the tracks of super typhoon are mainly affected by variations in the warm pool and subtropical Northwestern Pacific High in the western Pacific. Copyright © 2012 John Wiley & Sons, Ltd.

Modulation of prostate cancer cell gene expression by cell-to-cell contact with bone marrow stromal cells or osteoblasts - Shuming Zhang; Jun Wang; Mehmet A. Bilen; Sue-Hwa Lin; Samuel I. Stupp; Robert L. Satcher (Clinical & Experimental Metastasis, 2009)

Prevention of TGF-β-induced apoptosis by interlukin-4 through Akt activation and p70S6K survival signaling pathways - Sue-Jane Lin; Chungming Chang; Ah-Kau Ng; Shu-Han Wang; Jia-Je Li; Cheng-po Hu (Apoptosis, 2007)

The central role of osteoblasts in the metastasis of prostate cancer - Michel B. Choueiri; Shi-Ming Tu; Li-Yuan Yu-Lee; Sue-Hwa Lin (Cancer and Metastasis Reviews, 2007)

Over-expressed estrogen receptor-α up-regulates hTNF-α gene expression and down-regulates β-catenin signaling activity to induce the apoptosis and inhibit proliferation of LoVo colon cancer cells - Hsi-Hsien Hsu; Sue-Fei Cheng; Li-Mien Chen; Jer-Yu Liu; Chun-Hsien Chu; Yi-Jiun Weng; Zih-Ying Li; Chung-Sheng Lin; Shin-Da Lee; Wei-Wen Kuo; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2006)

Fine-tuning risperidone dosage for acutely exacerbated schizophrenia: clinical determinants - Hsien-Yuan Lane; Yue-Cune Chang; Chih-Chiang Chiu; Sue-Hong Lee; Cher-Yeang Lin; Wen-Ho Chang (Psychopharmacology, 2004)

Yeast consensus initiator sequence markedly enhances the synthesis of metallothionein III in Saccharomyces cerevisiae - Sue-Hong Wang; Yang-Hsin Shih; Lih-Yuan Lin (Biotechnology Letters, 1998)